Comparison of oral and video debriefing and its effect on knowledge acquisition following simulation-based learning. (5th January 2017) - Farooq, Omer; Thorley-Dickinson, Victoria A; Dieckmann, Peter; Kasfiki, Eirini V; Omer, Rasha M I A; Purva, Makani
Abstract : Introduction: Learning from simulation takes place to a large extent in debriefing; however, there is still sparse knowledge about the advantages and disadvantages of debriefing methods. 2 common forms are video-assisted and oral only debriefing. We set out to determine if there is increased knowledge acquisition for candidates undergoing video, rather than oral debriefing. Methods: Second year doctors were randomised to a training day with oral or video feedback. Candidates underwent an emergency clinical scenario followed by feedback. The candidates completed 30 multiple choice questions related to managing common clinical emergencies presimulation and postsimulation training. Results: There was no significant difference in the postscore mean for the oral debriefing (128.3, SD 5.16) and video-assisted debriefing group (127.1, SD=5.96). There was significant interaction between precourse and postcourse scores with superior knowledge acquisition for candidates with lower precourse scores (p=0.008). The candidates with lowest precourse score showed significant improvement in the orally debriefed group in comparison to video debriefed group. Discussion: Our results showed that video debriefing has equivocal effect to oral debriefing. Oral debriefing provides superior knowledge acquisition to learners with lower precourse test scores.